2018
DOI: 10.24203/ajbm.v6i5.5489
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Training on Organizational Performance

Abstract: Training is one of the Human Resources functions of the organization. When employees are recruited into the organization, they may not come with all the required skill set to discharge fully their roles in the organization. Hence, the one to equip such new employees with relevant skill set for the good of the organization. Also, the business world is very dynamic and ever changing. Organizations keep innovating making it imperative or organizations to keep training and learning. The rate technological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 5 publications
4
18
0
Order By: Relevance
“…Training is a vital component for the hospitality industry to attain organisational performance. A well-designed training program leads to a high level of organisational performance (Daniel, 2018). Training provided to the employees is transferred into organisational performance through employee satisfaction and employee performance (Nassazi, 2013;Imran & Tanveer, 2015).…”
Section: Organisational Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Training is a vital component for the hospitality industry to attain organisational performance. A well-designed training program leads to a high level of organisational performance (Daniel, 2018). Training provided to the employees is transferred into organisational performance through employee satisfaction and employee performance (Nassazi, 2013;Imran & Tanveer, 2015).…”
Section: Organisational Performancementioning
confidence: 99%
“…2002) have also discovered in their research that training is unlikely to create positive changes in job satisfaction or organizational performance. This belief is contradicted by (Garavan et al, 2021;Kanapathipillai & Azam, 2020;Samwel, 2018;Gobal et al, 2018;Daniel, 2018;David et al, 2005;Jenks et al, 2007) who clarified that employee can increase their intelligence, adeptness and aptitude through training programs that are well designed. Moreover, the training programs impart knowledge that could be shared by all trainees' which would lead to job satisfaction (Gobal et al, 2018) and ultimately enhance organisational performance (Karim et al, 2019).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Strategy refers to various managerial decisions and actions to distinguish the company from competitors and maintain its competitive advantage. The company's strategy must be following its mission, resources, and environmental circumstances (Daniel, 2018). A marketing strategy is a strategy that organizations use to provide their target customers with quality products at affordable prices, offer effective promotional strategies, and interact with their distribution outlets, thus creating demand for their products and improving performance (Gituma, 2017).…”
Section: Literature Review Sales Marketing Strategymentioning
confidence: 99%
“…A study by Olaniyan and Ojo (2008), and Naqvi and Khan (2013) revealed that training has a significant positive relationship with organisational performance. The positive impact between training and organisational performance is that increased employees' skill, knowledge, and ability gained from training affects employees' commitment to the organisation, resulting in better productivity (Daniel, 2018). Therefore, it is necessary to improve and apply training as part of organisational agendas to achieve organisational objectives.…”
Section: Relationship Between Training Policy and Asset Management Performancementioning
confidence: 99%